2017
DOI: 10.1177/1545968317712469
|View full text |Cite
|
Sign up to set email alerts
|

Rehabilitation for Individuals With Genetic Degenerative Ataxia: A Systematic Review

Abstract: There is consistent evidence that rehabilitation improves function, mobility, ataxia, and balance in genetic degenerative ataxia.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
49
1
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 70 publications
(73 citation statements)
references
References 53 publications
4
49
1
2
Order By: Relevance
“…Historically, in line with the classical view of the CB as a motor center, the main focus of rehabilitation approaches has been on motor aspects, mainly ataxia and dysmetria [135,136], although there is limited evidence about their effectiveness [137][138][139][140].…”
Section: Introducing Cognition Into Cerebellarmentioning
confidence: 99%
“…Historically, in line with the classical view of the CB as a motor center, the main focus of rehabilitation approaches has been on motor aspects, mainly ataxia and dysmetria [135,136], although there is limited evidence about their effectiveness [137][138][139][140].…”
Section: Introducing Cognition Into Cerebellarmentioning
confidence: 99%
“…Despite these limitations, some reviews reported on adverse events and recommended exercise to be safe (27,36,45,46,50,58). Other reviews recommended caution when interpreting findings (16,48,49,53), due to heterogeneity in intervention characteristics, outcome measures, insufficient high-quality studies and likelihood of Type II errors.…”
Section: Physical Activity Interventionsmentioning
confidence: 99%
“…One review investigated the effect of multidisciplinary care, including a consultant in rehabilitation, occupational therapist, physical therapist, speech-language pathologist, dietician, and social worker (44). Two reviews (16, 52) addressed the effect of combined interventions in individuals living with HD, including: exercise individualised addressing maintenance of functional ability, flexibility, strength, video based exercise designed to reduce impairment and promote balance, physiotherapist instructed stretches, coordination, balance, one leg balance and tandem walking and upper limb ball exercises, respiratory intervention, facial exercise, whole body exercises in lying standing and sitting for gait, transfer training, postural training, a multi-sensory stimulation intervention, gait therapy, cycling, resistance exercises and aerobic exercise, use of videogames, PNF intervention, functional activities, combination with occupational therapy and social activities.Four systematic reviews(41,42,53,54) addressed the effect of combined interventions in individuals living with ataxias, including: coordination, balance, and muscular conditioning exercise, physical therapy, with a focus on balance, gait, general conditioning, muscle strength and range of motion, coordinative training with the main goal of being able to activate and engage/control mechanisms of balance, multi-joint coordination, occupational therapy (daily activities such as accessing to food, clothing, personal hygiene, and leisure were some of the main disabilities focused by these patients).Two systematic reviews(55,56) addressed the effect of combined interventions in individuals living with PSP, including: balance training complemented with eye movement and visual awareness training (versus balance training alone and limb coordination activities), fine motor activities, tilt board balancing, ambulation training, exercises to improve strength and coordination, static and dynamic balance, resistive and isokinetic exercises, Biomechanical Ankle Platform System, physical exercises, modified body weight support treadmill, wearable audio-biofeedback device/Dynamic Antigravity Postural System; Vibration Sound system, exercise programme of stretching, treadmill with and without body weight support, physical therapy exercises and Xbox Kinect, Virtual Gaming System, robot-assisted gait training, using end-effector robotic rehabilitation locomotion training (G-EO system device), multidisciplinary intensive rehabilitation treatment.Muscle strength trainingTwo systematic reviews(28,57) included interventions lasting from 12 to 52 weeks and investigating strength training in individuals living with NMDs, including: general muscle involvement or selected muscles, dynamic and isometric strength training with weights. Frequency of interventions was not reported in both studies, while intensity ranged between 30 and 60 minutes per session.Aerobic trainingOne systematic review included three non-randomised studies lasting 8 to 32 weeks and investigating aerobic training such as walking and cycling in individuals living with NMDs.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…The benefit of physiotherapeutic intervention is under dispute for patients with degenerative ataxia since the cerebellum is known to play an important role in the generation and adaptation of appropriate patterns of limb movements and dynamic control of balance [8][9][10]. in a systematic review by Milne et al [11], evaluating rehabilitation interventions for individuals with genetic degenerative ataxia, 5 randomized controlled trials with 292 participants were included. The rehabilitation interventions involved coordination and balance training, multifaceted inpatient rehabilitation, a cycling regime, balance exercises with technology-assisted biofeedback, respiratory muscle training, and treadmill training.…”
Section: Introductionmentioning
confidence: 99%